2021
DOI: 10.1177/14759217211038065
|View full text |Cite
|
Sign up to set email alerts
|

A feature learning-based method for impact load reconstruction and localization of the plate-rib assembled structure

Abstract: Impact load is the load that machines frequently experienced in engineering applications. Its time-history reconstruction and localization are crucial for structural health monitoring and reliability analysis. However, when identifying random impact loads, conventional inversion methods usually do not perform well because of complex formula derivation, infeasibility of nonlinear structure, and ill-posed problem. Deep learning methods have great ability of feature learning and nonlinear representation as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…where u is a coefficient that changes with iteration. Since there are multiple local optimal solutions to Equation (17), the Nesterov's acceleration process is improved by adding a judgment step to achieve a continuous minimization of the objective function. From the above derivation, an AGSTA can be summarized as Algorithm 2.…”
Section: Solution Strategy For the Fogsl P Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where u is a coefficient that changes with iteration. Since there are multiple local optimal solutions to Equation (17), the Nesterov's acceleration process is improved by adding a judgment step to achieve a continuous minimization of the objective function. From the above derivation, an AGSTA can be summarized as Algorithm 2.…”
Section: Solution Strategy For the Fogsl P Methodsmentioning
confidence: 99%
“…Qiu et al 16 localized impact forces on a steel panel by using the pattern recognition method and reconstructed the time history of impact force via the Tikhonov regularization method, which are two separate processes. Chen et al 17 used two different deep neural networks for localization and time history reconstruction of the impact force separately, while a large amount of data was required to train the networks.…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that their prediction accuracy was improved while maintaining the computational effort. Chen et al [77] proposed a feature-based DL method for impact load localization of a plate structure. They used two LSTM layers and a BiLSTM layer with uniform distribution to learn the connection between input and load in time steps.…”
Section: Lstmmentioning
confidence: 99%
“…After their work, other researchers tried to enhance their results. For example, Chen et al [77] proposed a feature learning-based method for impact load localization plate structures. They also used a Bi-LSTM and two LSTM layers to learn the relationship between inputs and output.…”
Section: Bi-lstmmentioning
confidence: 99%
See 1 more Smart Citation